A tribocorrosion investigation of SLM fabricated ti6al4v nanocomposites by laser rescanning and GO mixing. Issue 1 (2nd August 2021) - Lu, Peipei; Wu, Meiping; Liu, Xin; Miao, Xiaojin; Duan, Weipeng
Abstract : Purpose: Ti6Al4V is a widely used metal for biomedical application due to its excellent corrosion resistance, biocompatibility and mechanical strength. However, a coupling reaction of friction and corrosion is the critical reason for the failure of implants during the long-term service in human body, shortening the life expectancy and clinical efficacy of prosthesis. Hence, this study aims to find a feasible approach to modify the service performances of Ti6Al4V. Design/methodology/approach: Selective laser melting (SLM), as one of the emerging metal-based additive manufacturing (AM) technologies is capable for fabricating patient-specific personalized customization of artificial prosthesis joints, owing to its high adaptability for complex structures. This study is concerned with the tribocorrosion behavior of SLM fabricated Ti6Al4V substrate enhanced by laser rescanning and graphene oxide (GO) mixing. The tribocorrosion tests were performed on a ball-on-plate configuration under the medium of simulated body fluid (SBF). Moreover, the surface morphologies, microstructures, microhardness and contact angle tests were used to further reveal the in-situ strengthening mechanism of GO/Ti6Al4V nanocomposites. Findings: The results suggest that the strengthening method of GO mixing and laser rescanning shows its capability to enhance the wear resistance of Ti6Al4V by improving surface morphologies and promoting the generation of hard phases. The wear volume of R-GO/Ti6Al4V is 5.1 × 10 −2 mm 3, which is 25.0% lower than that of pure SLM-produced Ti6Al4V. Moreover, a wear-accelerated corrosion of the Ti6Al4V occurs in SBF medium, leading to a drop in the open circuit potential (OCP), but R-GO/Ti6Al4V has the lowest tendency to corrosion. Compared to that of pure Ti6Al4V, the microhardness and contact angle of R-GO/Ti6Al4V were increased by 32.89% and 32.60%, respectively. Originality/value: Previous investigations related to SLM of Ti6Al4V have focused on improving its density, friction and mechanical performances by process optimization or mixing reinforcement phase. The authors innovatively found that the combination of laser rescanning and GO mixing can synergistically enhance the tribocorrosion properties of titanium alloy, which is a feasible way to prolong the service lives of medical implants.